PENGARUH APRESIASI SISWA TERHADAP PERTUNJUKAN MUSIK TRADISIONAL DENGAN HASIL BELAJAR MATA PELAJARAN SENI MUSIK KELAS 5 SDN SUKASARI 2 - M. Sulton Abdurrachim; Dinda Andiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the importance of learning music arts based on local culture as an effort to foster an attitude of respect for national culture and improve the quality of student learning outcomes in elementary schools. This study aims to determine the relationship between students' appreciation of traditional music performances and student learning outcomes in the Music Arts subject for fifth grade at SDN Sukasari 2, Sukasari Village, Cisaat District, Sukabumi Regency. This study uses a quantitative approach with a correlational research type. The sample in this study was all 25 fifth grade students, using a cluster sampling technique. The research instruments used consisted of a student appreciation questionnaire compiled using a Likert scale with five alternative answers, as well as a music arts learning outcome test. The data obtained were then analyzed using descriptive statistics and the Pearson Product Moment correlation test. The results showed that the level of student appreciation for traditional music performances was in the high category. This was indicated by the dominance of student answers in the agree and strongly agree categories on the appreciation questionnaire. Student learning outcomes also showed good achievements, with 92% of students obtaining scores above the Minimum Completion Criteria (KKM) set by the school. Furthermore, the correlation analysis revealed a positive relationship between students' appreciation of traditional music performances and their musical arts learning outcomes. Based on these findings, it can be concluded that students' appreciation of traditional music performances plays a crucial role in supporting successful musical arts learning. Therefore, local culture-based musical arts learning needs to be continuously developed to enhance students' appreciative attitudes and their learning outcomes.